Transparency and Conflict Resolution of Music Royalties in Indonesia: An Analysis of the Effectiveness of the National Collective Management Organization (LMKN) and Non-Litigation Mechanisms after Government Regulation No. 56 of 2021 - Elina Adi Wijayanti; Liana Setiawati (Fox Justi : Jurnal Ilmu Hukum, 2026)
The protection of songwriters’ economic rights in Indonesia faces significant challenges, particularly with respect to royalty payments in commercial public spaces and digital platforms. The main regulatory frameworks, Law No. 28 of 2014 on Copyright and Government Regulation No. 56 of 2021, aim to establish a “one-stop system” through the National Collective Management Organization (LMKN). Nevertheless, royalty disputes continue to occur, indicating gaps in transparency and dispute resolution mechanisms, as reflected in conflicts involving concerts and commercial venues. This study aims to (1) analyze the challenges and opportunities in implementing the principles of transparency and accountability within LMKN, particularly in relation to the Song and Music Information System (SILM), and (2) evaluate the effectiveness of non-litigation mechanisms (mediation and arbitration) as primary solutions for resolving music royalty disputes compared to litigation. This research adopts a normative-juridical legal method, employing a statute approach, conceptual approach, and case approach. Primary legal materials (Copyright Law and Government Regulation No. 56 of 2021) and secondary legal materials (literature, academic journals, and court decisions) are analyzed using a qualitative-descriptive method. The findings indicate that LMKN has not yet achieved full transparency and accountability due to limitations in the comprehensiveness of the SILM database. Mediation emerges as the most efficient dispute resolution mechanism, as litigation tends to be time-consuming and costly. Accordingly, LMKN should take a more proactive role as a mediator. In conclusion, legal certainty in royalty management requires institutional strengthening of LMKN and a cultural shift in dispute resolution from litigation toward non-litigation mechanisms.